Electro-optics handbook - Electro-optics handbook (McGraw-Hill, 2000)
The book overflows with 1.000 pages of hands-on technical assistance, accompanied by more than 500 helpful illustrations, detailed charts, diagrams, and data tables. It brings readers the latest advances in ever-shrinking elctro-optical circuitry, the entire range of lasers, and all types of X-ray, UV, and other electro-optical equipment.